HUBUNGAN POLA MAKAN KELUARGA DENGAN KEJADIAN OBESITAS PADA ANAK SEKOLAH DI RT. 006 RW. 069 KELURAHAN 16 ULU PALEMBANG - Siti Soleha (IKesT Muhammadiyah Palembang, 2024)
Background: Obesity is a pathological condition, namely the accumulation of excess fat than is required for normal body function. However, there are still many opinions in society that think that obese children are healthy. Objective: This research aims to analyze the relationship between family diet and the incidence of obesity in school children in RT 006 RW. 069 Subdistrict 16 Ulu Palembang. Methodology: The research method is collecting data by direct interviews with respondents and analyzing the data. Results: There were 75% of respondents adopting eating patterns that were not good for their children and 25% of respondents adopting eating patterns that were good for their children. Conclusion: This research shows a p value of 0.016, meaning there is a relationship between eating patterns and incidents. obesity in children with an OR of 8.31, meaning that children who adopt poor eating patterns have an 8.31 chance of experiencing obesity.